2012
DOI: 10.1039/c2cp22987k
|View full text |Cite
|
Sign up to set email alerts
|

High current density electrodeposition from silver complex ionic liquids

Abstract: Liquid metal salts are electrolytes with the highest possible metal concentration for electrodeposition, because the metal ion is an integral part of the solvent. This paper introduces the new ionic silver complexes [Ag(MeCN)(4)](2)[Ag(Tf(2)N)(3)], [Ag(MeCN)][Tf(2)N] and [Ag(EtIm)(2)][Tf(2)N], where MeCN stands for acetonitrile, EtIm for 1-ethylimidazole and Tf(2)N is bis(trifluoromethylsulfonyl)imide. These complexes have been characterized by differential scanning calorimetry, single crystal X-ray crystallog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
64
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 66 publications
(88 reference statements)
1
64
0
Order By: Relevance
“…[8][9][10][11][12][13] Several examples of electrodepositiono fm etals from liquid metal salts can be found in the literature. [14][15][16][17][18][19][20][21][22] Our research group has obtainedv ery promising resultsf or the electrodeposition of copper, [23][24][25] silver, [26][27][28][29][30] palladium [31] and lithium. [32] Metal coatings of ag ood quality were achieved at very high current densities,e ven withoutt he use of additives.…”
Section: Introductionmentioning
confidence: 98%
“…[8][9][10][11][12][13] Several examples of electrodepositiono fm etals from liquid metal salts can be found in the literature. [14][15][16][17][18][19][20][21][22] Our research group has obtainedv ery promising resultsf or the electrodeposition of copper, [23][24][25] silver, [26][27][28][29][30] palladium [31] and lithium. [32] Metal coatings of ag ood quality were achieved at very high current densities,e ven withoutt he use of additives.…”
Section: Introductionmentioning
confidence: 98%
“…Incorporation of metals into the cations or anions clearly can improve the dissolution of metal salts into ILs. 16 −18 In recent years, transition metal-containing ionic liquids (TM-ILs) have attracted intensive research interest, because of their many advantages over traditional ILs, such as a high solubility of metal salts, an unexpectedly strong response to an additional magnetic field, and a wonderful color rendering property. 19,20 Development of TM-ILs thus provides a great opportunity for task-specific ILs, which are promising alternatives to conventional ILs.…”
Section: Introductionmentioning
confidence: 99%
“…Low melting silver salts have been studied by the group of Binnemans for electrodeposition purposes. [18][19][20][21][22] It has been shown that by adding different ligands to the silver center, the melting point of usually high melting silver salts can be significantly reduced by disturbing the crystal packing. Depending on the number and structure of the ligand in combination with a suitable anion, melting points below 100 Synthetic procedures for the silver propene complexes…”
Section: Introductionmentioning
confidence: 99%